Quantitative Trait Loci for agronomic, pest resistance and end-use quality traits in a durum wheat doubled haploid population - Clarke F.R.; Knox R.E.; Clarke J.M.; Pozniak C.J. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Understanding the genetics of economic traits is important for breeding durum wheat (Triticum turgidum L. var durum). We identified DNA markers linked to various traits for use in marker-assisted selection. A set of 155 doubled haploid lines from a biparental cross were evaluated for phenotypic traits and scored for microsatellite and DArT(r) markers. A genetic map was constructed using JoinMap(r) and QTL analyses were performed. QTL were identified as follows for traits and chromosomes: maturity 2A, 2B, 4B; height 4B; lodging 2A, 4B; leaf spot 2A, 1B, 2B; stem solidness 3B; sawfly cutting 3B; yield 2B, 3B; test weight 2A, 2B, 4B; 1000 kernel weight 1A, 2A, 2B, 4B, 6B; protein content 4A, 4B; grain pigment 2A, 4B, 6B, 7B; gluten index 2A ,1B; sedimentation volume 2A, 1B, 6B. The markers should be useful in sawfly cutting 3B programs for the characterization of parental germplasm and selection for these traits in breeding populations.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)